The Impact of Food Prices Inflation on the Economic Growth of Pakistan: A Time Series Analysis (1990 – 2022) (Journal of Social Sciences Review, 2024)
This paper aims to analyzing the impact of food price inflation on the economic growth in Pakistan over the period 1990-2022. Food price inflation remained as a main challenge in the economy of Pakistan from the few years. Increasing cost of food items directly affect the poor households, reducing consumer purchasing power as they spend more than 70% of their income on just food items. The purpose of this paper is to prove the relationship between food price inflation and the economic growth in Pakistan. The present research makes Gross Domestic Product as the dependent variable and, Food Price Inflation, Imports, Exports, and Money Supply, as the independent variables of the research. Augmented Dickey Fuller test has been used in this research to determine the unit root of the time series. The long-run and short-run relationship have been examined by the use of the ARDL method over the period of 1990-2022. The empirical examination indeed provides an evidence that food price inflation has negative impact on economic growth in Pakistan in long-run. The short run dynamic error correction equation also showed that the coefficient of adjustment for the estimated food price equation is statistically significant at 5 percent level and negative.
Keywords: Gross Domestic Product; Food Price Inflation; Imports; Export; Money Supply